Stage T3 Squamous Cell Carcinoma Misdiagnosed as an Epidermal Inclusion Cyst. Issue 10 (6th October 2022) - Griffin, David; Griffin, Dallin; Kim, Seung-David; Polansky, Max
Abstract : Supplemental Digital Content is Available in the Text.